Analysis of The Evaluation of Existing Business Plan Development Methods ("Journal "U". Economy. Management. Finance.", 2021)
The article analyzes the evaluation of existing methods of developing a business plan. On the basis of the analysis, the features of various techniques are revealed. In conclusion of the article, the author formulated conclusions based on the conducted research.
Keywords: business plan; analysis; compilation; enterprise; planning; methods